Tasawuf Falsafi: Dalam Dua Dimensi Mistis dan Rasionalis - Ahmad Syatori, Syatori (Mahad Aly Al Fithrah Press, 2022)
This scientific discussion study in that reviews about scope of Sufism which highlights the combination of two sides or points of view between spirituality and rationality. The term Sufism is an expression that means about everything that seeks to cleanse the soul in order to get closer to Allah Swt. Sufism has many meanings and terms, all of which are the meaning of teachings about intentionality, glory and wisdom. This is far from various materialistic traits and worldly luxuries and always humbles itself to Allah Swt. The point of Sufism is all attitudes and behaviors and deeds that are based solely on Allah Swt. As for the term philosophical is an expression that contains meaning about everything that seeks to explain the meaning that can be accepted by the scientific mind. Philosophy has a meaning the value of wisdom in determining the attitude of thinking objectively, so as to produce a good and wise decision. With two approaches to meaning between Sufism and philosophy, the term philosophy Sufism can be understood as a whole as a form of fusion between heart and mind that merges into a new paradigm that gives birth to Sufism patterns with rational thinking patterns.